2016
DOI: 10.1163/15685314-04403003
|View full text |Cite
|
Sign up to set email alerts
|

Adulthood as Action

Abstract: Before the 1990s, Japanese routes to adulthood appeared to be well structured

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Non-marital childbearing is extremely rare and highly stigmatized (Hertog, 2009(Hertog, , 2011Raymo et al, 2015). National surveys on unmarried individuals have consistently and continuously shown that the great majority of singles intend or wish to marry (NIPSSR, 2022b), and numerous studies indicate persistent adherence to the marriage institution (e.g., Atoh, 1989Atoh, , 1994Atoh, , 2001Atoh et al, 2004;Cook, 2013Cook, , 2016aCook, , 2016bCook, , 2016cEndo, 2018;Nakano, 2010Nakano, , 2016Nakano, , 2022Nemoto, 2008;Nemoto et al, 2012;Yoshida, 2010aYoshida, , 2011Yoshida, , 2017.…”
Section: Cultural Theoriesmentioning
confidence: 99%
See 4 more Smart Citations
“…Non-marital childbearing is extremely rare and highly stigmatized (Hertog, 2009(Hertog, , 2011Raymo et al, 2015). National surveys on unmarried individuals have consistently and continuously shown that the great majority of singles intend or wish to marry (NIPSSR, 2022b), and numerous studies indicate persistent adherence to the marriage institution (e.g., Atoh, 1989Atoh, , 1994Atoh, , 2001Atoh et al, 2004;Cook, 2013Cook, , 2016aCook, , 2016bCook, , 2016cEndo, 2018;Nakano, 2010Nakano, , 2016Nakano, , 2022Nemoto, 2008;Nemoto et al, 2012;Yoshida, 2010aYoshida, , 2011Yoshida, , 2017.…”
Section: Cultural Theoriesmentioning
confidence: 99%
“…Family scholars of Japan (e.g., Hidaka, 2010; Lunsing, 2001; Tokuhiro, 2010) conclude that marriage is firmly considered to be the normal life path in Japan. Qualitative research on singlehood (Cook, 2013, 2014, 2016a, 2016b, 2016c; Dales, 2014; Dales & Yamamoto, 2019; Endo, 2018; Meagher, 2021; Nakano, 2010, 2014, 2016, 2022; Nemoto, 2008; Nemoto et al, 2012; Yoshida, 2010a, 2011, 2017) observes that most of their study participants want to marry. “I want to but am single/cannot marry” was a common sentiment shared by single interviewees in these studies, and some even emphasized to the researcher that they never meant to stay single (Yoshida, 2010a, 2011, 2017).…”
Section: Empirical Findings From Japanmentioning
confidence: 99%
See 3 more Smart Citations